2011
DOI: 10.1371/journal.pone.0025090
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Regulation of the Osmolyte Betaine Synthesizing Enzymes GSMT and SDMT from Halophilic Methanogen Methanohalophilus portucalensis

Abstract: The halophilic methanoarchaeon Methanohalophilus portucalensis can synthesize the osmolyte betaine de novo in response to extracellular salt stress. Betaine is generated by the stepwise methylation of glycine to form sarcosine, N, N-dimethylglycine and betaine by using S-adenosyl-L-methionine (AdoMet) as the methyl donor. The complete gene cluster of Mpgsmt-sdmt was cloned from Southern hybridization and heterologous expressed in E. coli respectively. The recombinant MpGSMT and MpSDMT both retained their in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 35 publications
4
49
0
1
Order By: Relevance
“…The pronounced sequence similarity between Mp GSMT and GNMT agrees with their overlapping activity as follows: both enzymes catalyze the SAM-dependent methylation of glycine to produce sarcosine2425. Structural analysis revealed that, similarly to all Class I methyltransferases, the catalytic core of GNMT adopts the Rossmann fold, which bears the SAM and substrate binding pockets262728.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…The pronounced sequence similarity between Mp GSMT and GNMT agrees with their overlapping activity as follows: both enzymes catalyze the SAM-dependent methylation of glycine to produce sarcosine2425. Structural analysis revealed that, similarly to all Class I methyltransferases, the catalytic core of GNMT adopts the Rossmann fold, which bears the SAM and substrate binding pockets262728.…”
supporting
confidence: 52%
“…However, there are outstanding distinctions between the two enzymes. First, while Mp GSMT is negatively regulated by the end product betaine25, the activity of GNMT is regulated by folate1430. Second, both glycine and sarcosine can be methylated by Mp GSMT25, whereas GNMT only acts on glycine3132.…”
mentioning
confidence: 99%
“…The synthesis pathway that rests on the methylation of glycine does not require the uptake of a precursor molecule and yields the intermediates monomethylglycine (sarcosine) and dimethylglycine (DMG) ( Fig. 1) (27,(30)(31)(32)(33).…”
mentioning
confidence: 99%
“…2). Betaine and DMSP are both osmolytes, which are molecules present in the cytosol of cells that regulate osmotic pressure as well as assist in maintaining protein structure (Yancey et al 1982).. Betaine, by far the largest contributor to the metabolite composition of the sinking particles, is an osmolyte utilized by organisms across the domains of life, although it is less commonly used in phytoplankton than DMSP (Yancey et al 1982;Boch et al 1997;Keller et al 1999;Lai and Lai 2011). Betaine concentrations can reach 170 mM inside a phytoplankton cell (Keller et al 1999), suggesting that this metabolite is likely to be measured at relatively high concentrations in particulate samples.…”
Section: Fluctuations Of Osmolytes On Sinking Particlesmentioning
confidence: 99%